Abdominal compliance. Issue 5 (May 2015) - Blaser, Annika Reintam; Björck, Martin; De Keulenaer, Bart; Regli, Adrian
<x xml:space="preserve">Abstract</x> ABSTRACT Abdominal compliance (AC) is an important determinant and predictor of available workspace during laparoscopic surgery. Furthermore, critically ill patients with a reduced AC are at an increased risk of developing intra-abdominal hypertension and abdominal compartment syndrome, both of which are associated with high morbidity and mortality. Despite this, AC is a concept that has been neglected in the past. AC is defined as a measure of the ease of abdominal expansion, expressed as a change in intra-abdominal volume (IAV) per change in intra-abdominal pressure (IAP): AC = ΔIAV / ΔIAP AC is a dynamic variable dependent on baseline IAV and IAP as well as abdominal reshaping and stretching capacity. Whereas AC itself can only rarely be measured, it always needs to be considered an important component of IAP. Patients with decreased AC are prone to fulminant development of abdominal compartment syndrome when concomitant risk factors for intra-abdominal hypertension are present. This review aims to clarify the pressure-volume relationship within the abdominal cavity. It highlights how different conditions and pathologies can affect AC and which management strategies could be applied to avoid serious consequences of decreased AC. We have pooled all available human data to calculate AC values in patients acutely and chronically exposed to intra-abdominal hypertension and demonstrated an exponential abdominal pressure-volume relationship. Most importantly, patients with high level of IAP have a reduced AC. In these patients, only small reduction in IAV can significantly increase AC and reduce IAPs. A greater knowledge on AC may help in selecting a better surgical approach and in reducing complications related to intra-abdominal hypertension.